(untitled) (Vietnam Journal of Community Medicine, 2026)
The study was conducted to evaluate the effectiveness of fungal infection control in medicinal plants at Nghe An Traditional Medicine Hospital. The study design was a non-randomized, non-controlled, before-and-after intervention. The sample size consisted of two storage warehouses and equipment such as air conditioners, dehumidifiers, thermometers, hygrometers, ventilation fans, and desiccant bags, along with 170 samples of medicinal plants at Nghe An Provincial Traditional Medicine Hospital. Techniques used included microclimate monitoring of the drug warehouses and fungal culture on Sabouraud agar. Results showed that before intervention, both the warehouses did not meet the required drug storage conditions with the average temperature at the four corners and the center of the warehouse of > 25ºC, humidity > 70%, and wind speed < 0.5 m/s. After 12 months of intervention, the average temperature at the four corners and the center of the warehouse was < 25ºC, humidity < 70%, and wind speed between 0.5 m/s and 1 m/s, meeting the required drug storage conditions. The overall prevalence of fungal infection in both the warehouses before intervention was 32.94% (56/170), which decreased to 22.35% (38/170) after 12 months of intervention; the intervention effectiveness was 32.15%. The prevalence of Aspergillus infection after 12 months of intervention dropped from 16.47% (24/170) to 6.47% (11/170); the intervention effectiveness was 54.15%.